Improvement of seismic behaviour of retaining walls by using cushions - Tunçay, Gözde Sezgin. (Thesis (Ph.D.)-Bogazici University.Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
Damages and collapses of retaining walls that occur after earthquakes cause loss of life and property and huge economic losses. The use of lightweight material as a cushion behind the retaining wall is one of the improvement methods. The main aim of this thesis is to evaluate the effectiveness and efficiency of a new proposed cushion layer as EPS beads and sand mixture (EPSB) for retaining structures. This cushion material placed behind the retaining wall was used for the first time in the literature. The effects of the mixture ratio and thickness of the EPSB cushion layer under different input motions were investigated. The other cushion layers as EPS geofoam and tire waste and sand mixture (TW) were also used. The performances of three cushion materials were compared with each other under the same input motions. In the experiments, a 1/15 scaled retaining wall model was designed to investigate the effectiveness of the cushion materials on the seismic performance of the retaining wall. Firstly, the experiments for the retaining wall model without cushion material were carried out on the shake table in the laminar box. In the second part, three different types of cushion materials were placed behind the retaining wall by changing thickness, density, and mixture ratios. EPS geofoam was found to provide the highest improvement performance compared to the TW and the EPSB cushions. Evaluation of the test results showed that the cushion type is significantly effective in improving the retaining wall model. Additionally, changes in thickness, density/mixing ratio, and input motions affect the results.
Keywords: Retaining walls -- Design and construction.; Retaining walls -- Earthquake effects.